Abundance estimates of Indo-Pacific humpback dolphins (Sousa chinensis) in Kuching Bay, East Malaysia - Poh, Anna Norliza Zulkifli; Cindy, Peter; Ngeian, Jenny; Andrew Alek, Tuen; Minton, Gianna (European Association for Aquatic Mammals, 2016)
Indo-Pacific humpback dolphins (Sousa chinensis, Osbeck, 1765) occur in shallow coastal waters from the east coast of India to central China and throughout Southeast Asia (Jefferson & Rosenbaum, 2014). While the species has been studied extensively in Hong Kong (e.g., Jefferson, 2000), China (Zhou et al., 2007; Chen et al., 2009, 2010), and Taiwan (Wang et al., 2007; Wang & Yang, 2011), very little is known about populations in Borneo, of which Sarawak is a part (Minton et al., 2016).